Extraction and characterization of essential oil of nutmeg (Myristica fragrans) fruit pericarp and utilization as a surface coating material to improve the shelf life of paneer - V. L. Vyshak; M. P. Rahila; I. Faisal; Smitha J. Lukose; Aparna Sudhakaran; S. N. Rajakumar (Journal of Veterinary and Animal Sciences, 2023)
Paneer is a traditional dairy product of India and is similar to unripened soft cheese. It is used as a raw material for the preparation of a variety of culinary dishes and snacks. Paneer is marble white in appearance, with a firm, cohesive and spongy body and a sweetish-acidic-nutty flavor. But it is highly perishable with a limited shelf- life like other indigenous dairy products. Its shelf life was reported to be only six days under refrigeration, though its freshness is lost within three days. The spoilage of paneer occurs mainly due to the growth of microorganisms, which bring about various physico-chemical changes. In the present study, attempts were made to increase the shelf-life of paneer at refrigerated storage by the application ofnutmeg pericarp essential oil surface coating. The essential oil was prepared from fresh nutmeg fruit flesh by steam distillation method. The physico-chemical and bio functional properties of essential oil were determined. The specific gravity and refractive index of the essential oil were found to be 0.903 and 1.477 respectively. The acid value and total polyphenolic value of essential oil were 3.36 and 4.04 mg GAE/g respectively. The essential oil was also found to have good antimicrobial and antioxidant activity. The shelf life of samples coated with essential oil packaged in LDPE pouches had more shelf life than the control paneer, as the coated paneer kept well for 9 days while the control paneer spoiled after the 6th day of refrigerated storage. The paneer with essential oil coating obtained satisfactory sensory scores